Rehabilitation Efficacy of Core Stability Training Combined with All-Round Intensive Exercise Training on Children with Spastic Cerebral Palsy - WANG Jing; YUE Ling; WANG Zexi; CHEN Zhihong; SUN Suzhen; MA Guilin; BAI Bing; CHEN Cuiying (康复学报)
ObjectiveTo investigate the rehabilitation effect of core stability training combined with all-round intensive exercise training on children with spastic cerebral palsy.MethodsA total of 144 children with spastic cerebral palsy treated in Children's Hospital of Hebei Province from September 2018 to August 2020 were divided into core stability group, intensive exercise group and combined group according to the experimental principle of 1∶1∶1 by stratified random method, with 48 cases in each group, and were provided with core stability training, all-round intensive exercise training, and core stability training + all-round intensive exercise training, respectively. The interventions for all three groups lasted for 6 months.The clinical efficacy of the three groups was statistically compared, as well as walking parameters (step length, width and speed), trunk control ability, Gross Motor Function Measure (GMFM), modified Ashworth scale (MAS) and Wee-Functional Independence Measure (WeeFIM) scores before intervention, and after 3 and 6 months of intervention.ResultsThe total effective rate of rehabilitation intervention in the combined group was higher than that in the core stability group and the intensive exercise group (P<0.05), respectively. After 3 and 6 months of intervention, the step length of the combined group was higher than that of the core stability group and the intensive exercise group (P<0.05) , and the step length of the intensive exercise training group was higher than that of the core stability group (P<0.05). The step width of the combined group after 3 and 6 months of intervention was lower than that of the core stability group and the intensive exercise group (P<0.05), and the step width of the intensive exercise group was lower than that of the core stability group (P<0.05). After 3 and 6 months of intervention, the average movement speed in the front and rear directions, the average movement speed in the left and right directions, the movement length and the WeeFIM score in the combined group were higher than those in the core stability group and the intensive exercise group respectively (P<0.05), and those of the core stability group was higher than those in the intensive exercise group (P<0.05). The scores of D and E areas of gross exercise in the combined group after 3 and 6 months of intervention were higher than those in the core stability group and the intensive exercise group (P<0.05). After 3 months and 6 months of intervention, MAS scores of the combined group were lower than those of the core stability group and the intensive exercise group (P<0.05), respectively, and those of the intensive exercise group was lower than those of the core stability group (P<0.05). There was no significant difference in the incidence of adverse reactions among the three groups (P>0.05).ConclusionAll-round intensive exercise training combined with core stability training can be applied to children with spastic cerebral palsy, and further improve their walking function, trunk control ability and motor function, and relieve their spastic conditions.